1996
DOI: 10.1002/(sici)1097-0290(19960405)50:1<1::aid-bit1>3.3.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

On the issue of interfacial activation of lipase in nonaqueous media

Abstract: The question of whether lipases can be activated by adsorption onto an interface in organic solvents was addressed using Rhizomucor miehei lipase as a model. In aqueous solution, this enzyme was shown t o undergo a marked interfacial activation. However, lipase (either Iyophilized or precipitated from water with acetone) suspended in ethanol or 2-(2-ethoxyethoxy)ethanol containing triolein exhibited no jump in catalytic activity when the concentration of triolein exceeded its solubility in these solvents, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 2 publications
1
33
0
1
Order By: Relevance
“…However no such activation was observed in a careful investigation into the existence of interfacial activation of lipase molecules in organic media. [27] For the lyophilised preparation, 70 % of the active sites were titrated after 96 h of titration ( Figure 1). It is possible that the remaining 30 % were reversibly denatured during the freezedrying step [5] or directly denatured by the solvent; this would explain why some proportion of the enzyme molecules are not available for catalysis.…”
Section: Resultsmentioning
confidence: 99%
“…However no such activation was observed in a careful investigation into the existence of interfacial activation of lipase molecules in organic media. [27] For the lyophilised preparation, 70 % of the active sites were titrated after 96 h of titration ( Figure 1). It is possible that the remaining 30 % were reversibly denatured during the freezedrying step [5] or directly denatured by the solvent; this would explain why some proportion of the enzyme molecules are not available for catalysis.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore attempted in the present work to compare a broad range of commercially available lipase preparations under identical reaction conditions. Hydrolysis of phosphatidylcholine (PC) in a reverse micellar system with sodium bis(2-ethylhexyl) sulfosuccinate (AOT) was chosen as the reaction for evaluating the reactivities of the lipases, our reasoning being that, because enzymes added to this system would be dissolved in the reverse micelles and adsorb onto the hydrophobic interface, they would be fully activated by what is known as "interfacial activation" (23), unlike in microaqueous organic media in which transesterification occurs (24).…”
mentioning
confidence: 99%
“…It has been suggested that the lower enzyme activity in organic solvent could be due to the fact that, after lyophilization, the enzyme is in a close conformation (less active) [24] . Then, if an additive (e.g.…”
Section: Why Do Additives Affect the Activity And Enantioselectivity mentioning
confidence: 99%